Contribution to the knowledge of the Croatian Pyraloidea fauna. Species reported from Biokovo Natural Park (Insecta: Lepidoptera) - Gumhalter, D.; Kucinic, M. (SHILAP Revista de lepidopterología, 2021)
Little is known on the occurrence of Pyraloidea species from Croatian mountains and there is no species list from Mountain of Biokovo. We provide new data on Pyraloidea species recorded from Biokovo Natural Park. The species list contains information on date and locality of species recorded during field surveys conducted by the first author between 2016 and 2019 and the second author between 1985 and 2018. During these field surveys, 71 Pyraloidea species were recorded. The list was complemented with six species known only from literature data. Altogether we report 77 Pyraloidea species, 54 belonging to the family Crambidae and 23 belonging to the family Pyralidae. This represents about 20,5% of the overall Croatian Pyraloidea fauna. Some interesting species that have been previously known only from historic literature are reported from Biokovo Mountain, for example, Catoptria acutangulella (Herrich-Schäffer, 1847), a montane specie that has not been recorded in Croatia since 1896 and Biokovo Mountain since 1850 (the results have been published elsewhere). The species Mecyna trinalis ([Denis & Schiffermüller], 1775) has been recorded for the first time in Dalmatia. The species Udea numeralis (Hübner, [1796]), Evergestis limbata (Linnaeus, 1767) and Hypsopygia fulvocilialis (Duponchel, 1834) have been reported for the first time from Dalmatia in almost 150 years and the species Selagia spadicella (Hübner, [1796]), Agriphila inquinatella ([Denis & Schiffermüller], 1775) and Agriphila straminella ([Denis & Schiffermüller], 1775) have been reported for the first time in almost 100 years. Also, 15 species have been reported for the first time from Dalmatia in decades, like Dolicharthria bruguieralis (Duponchel, 1833), a species that has not been reported in almost 85 years. This paper deepens the knowledge on the distribution of Pyraloidea species occurring in Biokovo Natural Park and reconfirms the occurrence of many species that have not been reported from Croatia in decades.